Accuracy Analysis on Dual Pressure (Positive and Negative) Calibrator Design to Investigate the Sensor Response - Abdi Wibowo; Triana Rahmawati; Priyambada Cahya Nugraha; I Dewa Gede Hari Wisana; Honey Honey; Mansour Asghari (Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2022)
Calibration is an activity to determine the conventional correctness of the value of measuring instrument designation and measuring material by comparing against the measuring standards that are traced to national or international standards. A sphygmomanometer is a device used to measure blood pressure. Suction pump is a tool to suck various types of fluid formed from the body's secretion process that under certain conditions need to be cleaned. DPM (Digital Pressure Meter) is a tool for calibrating sphygmomanometers and suction pumps. Therefore, it takes a calibrator device to calibrate both tools. The purpose of this study was to determine the sensor response and analyze the accuracy of the design of a dual pressure calibrator (+ and -) that can be used for two devices at once (sphygmomanometer and suction pump) using one sensor (pss-C01V-R18 autonics). The research was conducted at the Campus of the Department of Electrical Engineering Of The Ministry of Health Surabaya, first the data was taken from three different brands of sphygmomanometer and suction pump, the second data was taken using module calibrators, and the third data collection from modules and comparison tools (DPM). In this study successfully measured positive and negative pressure with autonics sensors, the results obtained are accurate in accordance with the results of standard tools. The result of this tool can be used for dual pressure calibrators using autonics sensors.